Guidelines for developing quantitative safety risk criteria (J. Wiley, 2009)
Written by a committee of safety professionals, this book creates a foundation document for the development and application of risk tolerance criteria. It helps safety managers evaluate the frequency, severity and consequence of human injury ; Includes examples of risk tolerance criteria used by NASA, Earthquake Response teams and the International Maritime Organization, amongst others ; Helps achieve consistency in risk-based decision-making ; Reduces potential liabilities in the use of quantitative risk tolerance criteria through reference to an industry guidance document.